2021
DOI: 10.1016/j.celrep.2021.109224
|View full text |Cite
|
Sign up to set email alerts
|

Human amyotrophic lateral sclerosis excitability phenotype screen: Target discovery and validation

Abstract: Highlights d ALS patient-derived motor neurons are hyperexcitable d A high-throughput GCaMP screen is used to identify ALS excitability modulators d Kv7 ion channels, AMPA receptors, and the type 2 dopamine receptor are major targets d The D2 dopamine receptor modulates both neuronal excitability and survival

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…The first of these therapeutic clinical candidates, identified in 2015, was the Kv7 channel activator Retigabine/Ezogabine, a known anti-epileptic drug (Wainger et al, 2014;Wainger et al, 2020). Neuronal hyperexcitability is a significant pathophysiological mechanism in ALS (Vucic et al, 2008;Fogarty, 2018;Huang et al, 2021). Through electrophysiological analysis using multielectrode arrays, the Eggan team demonstrated that Retigabine/Ezogabine was capable of suppressing the hyperexcitability of ALS iPSCderived MNs (Wainger et al, 2014).…”
Section: Using Human Motor Neurons Generated From Pluripotent Stem Cells To Perform In Vitro Drug Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these therapeutic clinical candidates, identified in 2015, was the Kv7 channel activator Retigabine/Ezogabine, a known anti-epileptic drug (Wainger et al, 2014;Wainger et al, 2020). Neuronal hyperexcitability is a significant pathophysiological mechanism in ALS (Vucic et al, 2008;Fogarty, 2018;Huang et al, 2021). Through electrophysiological analysis using multielectrode arrays, the Eggan team demonstrated that Retigabine/Ezogabine was capable of suppressing the hyperexcitability of ALS iPSCderived MNs (Wainger et al, 2014).…”
Section: Using Human Motor Neurons Generated From Pluripotent Stem Cells To Perform In Vitro Drug Testingmentioning
confidence: 99%
“…The positive action of Ropinirole in ALS MNs is not fully understood yet, but it was proposed to be linked with the reduction of toxic neuronal hyperexcitability via Dopamine D2R activation (Okano et al, 2020). Other studies have also recently identified D2 dopamine receptors as significant modulators of ALS MN excitability (Huang et al, 2021). Interestingly, the beneficial effects of Ropinirole were also identified in non-SOD1 sALS MNs, but not in SOD1-mutant ALS models (Fujimori et al, 2018).…”
Section: Using Human Motor Neurons Generated From Pluripotent Stem Cells To Perform In Vitro Drug Testingmentioning
confidence: 99%
“…Another recent study used a chemogenomic library of 2899 compounds, 67 of which reduced the hyperexcitability of ALS motor neurons carrying the SOD1(A4V) mutation. The targets include two known ALS excitability modulators, AMPA receptors, Kv7.2/3 ion channels, and D2 dopamine receptors as modulators [ 210 ]. These studies provide evidence for the successful use of hiPSCs for screening or existing drugs for advancement to clinical trials for the potential treatment of ALS.…”
Section: Disease Modeling Using Hipscsmentioning
confidence: 99%
“…C9ORF72 RE motor neurons also demonstrated an increase in the expression of SK channel subunits, which could be corrected using specific inhibition of the SRSF1-dependent nuclear export of pathological C9ORF72 RE transcripts ( Castelli et al, 2021 ). Contrastingly, hyperexcitability in lower motor neurons has been established in several other ALS models and studies have used pharmacological activators of Kv7 potassium ion channels to reduce hyperexcitability in C9ORF72 RE -derived motor neurons with the possibility that they protect motor neurons from excitotoxicity ( Wainger et al, 2014 ; Huang et al, 2021 ). These studies have now been translated into clinical trials ( Wainger et al, 2021 ).…”
Section: Lower Motor Neuron Dysfunction In C9orf72 Re -Mediated Amyotrophic Lateral Sclerosis- Frontotempormentioning
confidence: 99%